Gestational Trophoblastic Neoplasia with Hyperthyroidism - Devi Rahmadhona; Betty Agustina Tambunan (Indonesian Association of Clinical Pathologist and Medical laboratory, 2020)
Gestational Trophoblastic Neoplasia (GTN) is a malignant lesion arising from placental villous and extra-villoustrophoblastand occurs in 1:40,000 pregnancies. Invasive mole and choriocarcinoma are the vast majority of GTN whichproduce substantial amounts of Human Chorionic Gonadotropin (hCG). Hyperthyroidism in GTN is due to the stimulation ofthe thyroid gland by hCG which has a similar structure with Thyroid-Stimulating Hormone (TSH). A 28-year-old female,suspected with choriocarcinoma and anemia, had a history of recurrent vaginal bleeding for eight months, accompaniedwith loss of appetite, weight loss, palpitation, and tremor. Physical examination such as pulse rate of 114x/minutes, the0 respiration rate of 26x/minutes, temperature 38 C, conjunctival anemia, and dyspnea were reported. In addition, laboratoryfindings such as anemia, leukocytosis, hypoalbuminemia, hypokalemia, increase of LDH, increase of hCG >1,500,000mIU/mL, T4 levels of 14.1 ug/dL (4.40-10.90 ug/dL), FT4 levels of 1.95 ng/dL (0.89-1.76 ng/dL), and decrease of TSH were alsoreported. Abdominal CT Scan suggested uterine mass suspected as malignancy infiltrating to the rectum with metastaticfeatures in the liver, base of left lung, spleen and left kidney. Increased CA-125, and metastatic features of lung rightparacardial and left suprahilar from Chest X-ray were found. Diagnostic criteria for gestational trophoblastic neoplasia are asfollows: increased hCG 4 x tests; increased hCG three weekly tests; histology diagnosis of choriocarcinoma; increased hCG> 20,000 more than four weeks post evacuation and the presence of metastasis. Hyperthyroidism in GTN is potentiallylife-threatening because of heart failure and thyroid storm. Hyperthyroidism increases morbidity and mortality in GTNpatient; therefore, periodic thyroid tests is essential to prevent further complication of hyperthyroidism.